Evaluation of single crystal elastic constants and stacking fault energy in high-nitrogen duplex stainless steel by in-situ neutron diffraction. (1st July 2016) - Kim, Yanghoo; Kim, Yong Min; Koh, Ji-Yeon; Lee, Tae-Ho; Woo, Wan Chuck; Han, Heung Nam
Abstract: Single crystal elastic constants of austenite and ferrite phases in high-nitrogen duplex stainless steel were evaluated by an elastic self-consistent model combined with an optimization process using in-situ neutron diffraction data. The optimized elastic constants were validated by the indentation moduli of each phase obtained by nanoindentation. In addition, the stacking fault energy of austenite was evaluated based on the neutron diffraction profile and the single crystal elastic constants and was subsequently correlated with the observed deformation microstructure. Graphical abstract: